Invertebrate DNA metabarcoding reveals changes in communities across mine site restoration chronosequences - Fernandes, Kristen; Van Der Heyde, Mieke; Megan, Coghlan; Wardell-Johnson, Grant; Bunce, Michael; Harris, Richard; Nevill, Paul (Wiley-Blackwell, 2019)
Invertebrate biomonitoring can reveal crucial information about the status of restoration projects; however, it is routinely underused because of the high level of taxonomic expertise and resources required. Invertebrate DNA metabarcoding has been used to characterize invertebrate biodiversity but its application in restoration remains untested. We use DNA metabarcoding, a new approach for restoration assessment, to explore the invertebrate composition from pitfall traps at two mine site restoration chronosequences in southwestern Australia. Invertebrates were profiled using two cytochrome oxidase subunit 1 assays to investigate invertebrate biodiversity. The data revealed differences between invertebrate communities at the two mines and between the different age plots of the chronosequences. Several characteristic taxa were identified for each age within the chronosequence, including springtails within the youngest sites (Order: Collembola) and millipedes within the oldest and reference sites (Order: Julida). This study facilitates development of a molecular “toolkit” for the monitoring of ecological restoration projects. We suggest that a metabarcoding approach shows promise in complementing current monitoring practices that rely on alpha taxonomy.